Procedure for assessing the investment attractiveness of foreign markets: Comparative analysis of former USSR countries - Andranik Muradyan (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2020)
One of the natural stages of development of the enterprise is the desire to expand its business abroad. Globalization, global trade integration, technology development, the emergence of political, economic, customs unions, the existence of international courts of arbitration, the emergence of elements of world culture and other factors reduce the barriers between potential investors and countries to internationalization. This phenomenon has a positive impact on the decisions of companies in diff erent parts of the world about the expansion abroad. The main goal of a foreign investor who plans to internationalize is making the most optimal choice of a foreign market where prevailing realities on business environment will enable the achievement of competitive advantage. Because of this, before internationalization, foreign investors should evaluate the investment attractiveness of all potential directions of internationalization in order to be able to realistically assess their own capabilities in these markets and assess all the risks and opportunities that may arise during the operation. The quality of the analysis which assess the level of investment attractiveness of potential directions has a large impact on the success of the company abroad. The article presents the procedure of comparative analysis taking as an example former USSR countries at the macro level.
Keywords: F23; F21; M31; M19; 650; Investment attractiveness of foreign markets; procedure of country attractiveness assessment; country attractiveness comparative analysis; foreign investments; USSR countries